N-type SnS2 thin films spray-coated from transparent molecular ink as a non-toxic buffer layer for solar photovoltaics. (1st September 2022) - Tair, Sabrina; Ghediya, Prashant R; Ech-Chergui, Abdelkader Nebatti; Guezzoul, M'hamed; Mukherjee, Sanat Kumar; Driss-Khodja, Kouider; Singh, Rajan; Ray, Jaymin; Amrani, Bouhalouane
Abstract: This paper reports the effect of solvent evaporation temperature on spray-coated tin disulfide (SnS2 ) thin films from molecular ink. Thiourea and tin chloride were the key chemical reagents used for the synthesis of SnS2 transparent ink under atmospheric conditions. The structural and compositional properties of SnS2 thin films revealed formation of pristine hexagonal SnS2 . The films are smooth, homogeneous resulting in band gaps ranging from 2 to 2.22 eV suited for a Cd-free alternative buffer layer for Cu-based multicomponent solar cells. Thermoelectric power measurement showed that tin disulfide films exhibit n-type conductivity. Activation energy estimated from temperature variation of electrical conductivity measurement varied from 40 to 90 mV. Our results suggest that ink-processed SnS2 can be used as a potential alternative for opto-electronic devices such as thin film solar cell and photodetector devices.